Comments on “The marine teleost fishes of the Sea of Marmara; an updated and annotated checklist” by Artüz & Fricke (2019) - Bilecenoglu, Murat (Zootaxa, 2020)
The recent paper by Artüz & Fricke (2019) is focused on the analysis of marine teleost fishes of the Sea of Marmara, where they have tried to correct doubtful species occurrences and presented an annotated checklist. In a few cases, the authors have provided convincing data for the removal of some species from the regional inventory, such as Apogon imberbis (Linnaeus, 1758), Scomberesox saurus (Walbaum, 1792) and Polyprion americanus (Bloch & Schneider, 1801), and pointed out revision-seeking genera (i.e. Alosa spp., Pegusa spp., etc.), which should certainly be taken into consideration. However, the paper also raises several doubts resulting from mistranslations of some previous research, misinterpretation and incomplete examination of certain published biodiversity data related to the Sea of Marmara. Despite the authors presented a number of mistaken first record data (for example Sardinella aurita Valenciennes, 1837, for full account see Bilecenoglu et al. 2002), included some unsubstantiated/questionable species (such as Symphodus melops (Linnaeus, 1758), Gobius vittatus Vinciguerra, 1883, etc.), and unexpectedly neglected the occurrence of some common coastal and deepsea species from the area, such as Arnoglossus kessleri Schmidt, 1915, Gobius bucchichi Steindachner, 1870, Labrus merula Linnaeus, 1758, Parablennius zvonimiri (Kolombatović, 1892) and Argyropelecus hemigymnus Cocco, 1829, I herein concentrate solely on the erroneous/invalid records (totaling 42 fish species) with appropriate explanations.